Apparatus and Periosteum Fenestrated Rafia in transverse fractures irreducibility - Quesada, Fortunato (1936)
We all agree that the ideal treatment of a fracture is a perfect reduction, holistic biological basis of reconstitution of the injured segment. In a large group of fractured, this ideal can not be achieved by the opposition of the peaks in the oblique fractures and tisural interposition in the transverse ab, consisting of muscle fragments, fascial, periosteal or bone, allow external maneuvers for activated drive, with or without passive prosthesis, reduce thrust, angulation and rotation, but prevent displacement to remove the fracture surfaces, with intervening elements, which is a favorable condition for the pseudo-arthrosis or consolidations defective, anatomically and physiologically speaking.